Theoretical study of a single-walled carbon nanotube and a cellulose biofiber as 5-fluorouracil anti-cancer drug carriers - Abdullah, Eshraq Ahmed (European Journal of Chemistry, 2022)
Chemotherapy is one of the most valuable and widely available option in cancer treatment. However, a method of delivering the drug to achieve a therapeutic effect still a considerable challenge. Therefore, this study seeks to identify the non-bonding interaction of 5-fluorouracil anticancer drug with a single walled carbon nanotube and a Cellulose bio-fiber using density functional theory and molecular mechanics simulations. To do that, adsorption locator and DMol3 modules were utilized to determine the electronic and optical properties of carriers before and after adsorption processes. The interaction energies indicate that the 5-fluorouracil molecule can physically adsorb and the optimized geometries are stable. The charge transfer occurs between N4-H10 bond of the 5-fluorouracil molecule and the cellulose carrier by a synergistic effect of hydrogen bond formation and van der Waals forces. This effect smoothly transforms into van der Waals interactions by O3, N4, and N5 atoms in the case of single-walled carbon nanotubes. There is a clear difference in the absorption peak and a significant narrowing of the molecular energy gap of a cellulose complex because of the shifting of the electron accepting center to a drug molecule. The conductor-like screening model shows the affinity of the complexes toward hydrogen bond acceptor, which enhances their solubility in biological systems. A remarkable influence in the case of the cellulose complex works as a starting point to use natural polymers as drug delivery carriers.